M10 Persistence on antifibrotic medication in idiopathic pulmonary fibrosis (IPF) is not dependent on distance travelled to tertiary centre. (12th November 2019) - Babu, A; McLellan, T; Verghese, P; Harris, E; Harding, K; Simler, N; Fiddler, C; Parfrey, H; Woodhead, F; Thillai, M
Abstract : Antifibrotic medications (pirfenidone or nintedanib) are recommended in IPF patients who meet lung function criteria. Whilst effective in slowing FVC decline, they are associated with side-effects including GI disturbance, fatigue and skin rash. Discontinuation rates as a result of these effects have been reported as high as 21% for Pirfenidone and 26% for Nintedanib. 1 2 Currently, Royal Papworth is the largest prescriber of antifibrotics in the East of England and patients travel up to 2.5 hours (sometimes on smaller A roads) to attend outpatient clinics. Our aim was to investigate whether there is a correlation between distance travelled and drug persistence. We performed a retrospective analysis of 447 patients with IPF treated from 2013 to 2019. All patients started on medication are recorded on a database; this was accessed on 25/06/19. Data on drug persistence was coupled with patient postcode. Statistical analysis was performed with Graphpad Prism. The majority of patients (95%) travelled less than 135 km. The furthest distance was 577 km (Truro), figure 1a. Median distance was 71 km, mean 78 km (mean time by car was 61 minutes) and mode 60 km. A heatmap (performed using BatchGeo software) showed a clustering of postcode data around 17 towns (figure 1b). We then performed an analysis based on whether patients persisted on drug at 0–3 months, 3–6 months or >6 months (figure 1c). This showed no difference across 9 geographical clusters. We next performed a complete analysis of distance travelled from postcode vs. persistence (in months) on antifibrotic for all 447 patients and found no correlation (figure 1d). Our data suggest that distance travelled does not appear to be a factor in drug persistence. This is important as many IPF patients are elderly (the mean age in our data set was 71 years) yet remain keen to travel to our centre, despite the long journey. We have initiated shared care to alternate visits between our hospital and their referring centres and this (in conjunction with virtual clinics) may be an improved method of managing patients with IPF, given the lengths they travel to get treatment. References: Barrat S, et al . 2018. Galli JA, et al . 2017.